2013
DOI: 10.4049/jimmunol.1300303
|View full text |Cite
|
Sign up to set email alerts
|

Y Chromosome–Linked B and NK Cell Deficiency in Mice

Abstract: There are no primary immunodeficiency diseases linked to the Y chromosome, because the Y chromosome does not contain any vital genes. We have established a novel mouse strain in which all males lack B and NK cells and have Peyer’s patch defects. By 10 wk of age, 100% of the males had evident immunodeficiencies. Mating these immunodeficient males with wild-type females on two different genetic backgrounds for several generations demonstrated that the immunodeficiency is linked to the Y chromosome and is inherit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…Notwithstanding, it is worth noting that a spontaneous deletion in the long arm of ChrY has been shown to influence lymphocyte development (49), raising the possibility that the genome-wide regulatory activity of ChrY also may involve changes in the spatial positioning of X-linked and autosomal genes associated with transcription, that is, movement toward or away from transcriptional centers (50). Our findings demonstrate that ChrY variants regulate the expression of small RNAs with striking directionality (Fig.…”
Section: Copy Number Variation In Chry Multicopy Genes Does Not Corrementioning
confidence: 60%
“…Notwithstanding, it is worth noting that a spontaneous deletion in the long arm of ChrY has been shown to influence lymphocyte development (49), raising the possibility that the genome-wide regulatory activity of ChrY also may involve changes in the spatial positioning of X-linked and autosomal genes associated with transcription, that is, movement toward or away from transcriptional centers (50). Our findings demonstrate that ChrY variants regulate the expression of small RNAs with striking directionality (Fig.…”
Section: Copy Number Variation In Chry Multicopy Genes Does Not Corrementioning
confidence: 60%
“…A recent publication (Sun et al 2013) presented evidence of a potential link between Y chromosome deletion and B and NK cell deficiencies. To investigate potential differences in the immune characteristics between B6JBom and B6NTac, a multiparametric flow cytometry analysis of spleen and bone marrow cells was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al (2013) reported a B and NK cell deficiency in the bone marrow of mice which was linked to a Y chromosome deletion of 1/3 of its length but were not able to determine how the Y chromosome deletion mediated B and NK cell defects. Here, we have shown differences between B6JBom and B6NTac in respect to spleen size and characteristics of immune and non-immune spleen cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on May 11, 2018 -Published by genome.cshlp.org Downloaded from protein-coding sequences as determined by exome sequencing, or due to expression differences in ChrY genes as determined by microarray and qPCR, but is rather due to a structural mutation arising from the deletion of one-third of the entire ChrY (Sun et al 2013). Therefore, this new study supports the structure of ChrY's long arm as the genetic element exerting gene regulatory properties in immune cells.…”
Section: Global Gene Regulation By the Mammalian Y Chromosomementioning
confidence: 99%
“…Therefore, the nature of ChrY has led to the consensus that it is primarily composed of ''junk'' DNA whose contribution to phenotypic differences among the sexes is limited to sexual development and spermatogenesis. Indeed, until recently, large deletions in the long arm of the murine ChrY had no overt phenotypic effects except on spermatogenesis and sex ratio distortion (Tiepolo and Zuffardi 1976;Styrna et al 1991a,b;Sun et al 2013).…”
mentioning
confidence: 99%